Relationship between dietary intake, eating attitudes, and premenstrual syndrome severity among Iranian women: insights from a cross-sectional study - Sara Mighani; Fatemeh Taghizadeh Shivyari; Alireza Razzaghi; Mohammad Amerzadeh; Maryam Javadi (Journal of Eating Disorders)
Abstract Background Premenstrual syndrome (PMS) is a common issue that impacts many women, and a well-balanced diet can help alleviate PMS symptoms. Evidence suggests that dietary factors and eating disorders may influence PMS severity, yet the specific relationships remain unclear. This study aimed to evaluate the association of specific dietary components and eating behaviors with PMS symptoms. Methods This cross-sectional study was conducted on 252 women with PMS who were referred to healthcare centers in Qazvin province. Data concerning PMS, dietary factors, and eating disorders were collected using online questionnaires, including the premenstrual symptoms screening tool (PSST), 3-day dietary recall, and Eating Attitudes Test-26 (EAT-26) questionnaires. Statistical analysis utilized ANOVA and chi-square tests. The adequacy of the sample was evaluated using the Kaiser-Meyer-Olkin (KMO) test. To examine the relationship between eating disorders, dietary factors, and PMS symptoms, multivariable linear regression analysis was conducted. Statistical significance was set at p < 0.05. Results According to the PSST, 28.7% of individuals reported mild severity, 21.9% reported moderate severity, and 49.4% reported severe severity. The study revealed that higher sodium (p = 0.003, OR = 1.000, 95% CI = [1.000, 1.001]), vitamin D (p = 0.044, OR = 1.298, 95% CI = [1.007, 1.674]), and vitamin C intake were positively linked to increased psychological PMS symptoms, (p = 0.036, OR = 1.006, 95% CI = [1.000, 1.012]) while magnesium showed a negative association with these symptoms. Also, sodium and vitamin D intake were significantly associated with increased physical symptoms (p < 0.05). Individuals with eating disorders showed higher rates of severe PMS symptoms, though differences were not statistically significant (p > 0.05). Conclusion These findings highlight the potential influence of specific nutrients on PMS severity. This insight could inform dietary recommendations for managing PMS symptoms, providing young women with potential non-pharmacological options to relieve discomfort.